Pengaruh Fasilitas Kampus, Kualitas Pengelolaan Parkir dan Dukungan Sosial Terhadap Motivasi Belajar Mahasiswa Universitas Pamulang - Faujan, Sanjun; Riyanto, Teguh; Alamsyah, Alamsyah (Jurnal Mahasiswa Manajemen, 2023)
Background – Campus facilities can increase students desire to be involved in the process of learning and are proven to influence study motivation. Campus facilities not only play a role in the learning process but also supporting facilities such as parking lots. Parking lots with good quality are at least able to protect student vehicles so that they can reduce distractions in the learning process. In addition to these two things, social support can also increase student learning motivation. High social support allows students to open opportunities for interaction in diverse environments and can actively access information that increases interest in learning. Objective – This study aims to determine the effect of campus facilities, the quality of parking management and social support on study motivation of student from Faculty of Economics and Business, Pamulang University. Design / Methodology / Approach – This study used a quantitative approach with an explanatory design. The population in this study were active students of the Faculty of Economics and Business, Pamulang University. The sample used in this study is 98 active students. The data used is primary data and comes directly from the answers to questionnaires Active students of the Faculty of Economics and Business, Pamulang University. Findings – The three independent variables including campus facilities, quality of parking management and social support, have a positive influence on study motivation of students from Faculty of Economics and Business, Pamulang University. Research Implication – This research can be used as information for education institutions, especially Pamulang University, to always maintain and improve the quality of campus facilities and parking management in order to increase student learning motivation. Limitations – This research was limited to Active Students of the Faculty of Economics and Business, Pamulang University